Mechanochemical Strategies for the Preparation of SiO2-Supported AgAu Nanoalloy Catalysts - da Silva, Rafael T. P.; Córdoba De Torresi, Susana I.; de Oliveira, Paulo F. M. (Frontiers in Chemistry, 2022)
Silver-gold nanoalloys were prepared from their metal salts precursor through bottom-up mechanochemical synthesis, using one-pot or galvanic replacement reaction strategies. The nanostructures were prepared over amorphous SiO2 as an inert supporting material, facilitating their stabilization without the use of any stabilizing agent. The nanomaterials were extensively characterized, confirming the formation of the bimetallic nanostructures. The nanoalloys were tested as catalysts in the hydrogenation of 2-nitroaniline and exhibited up to 4-fold the rate constant and up to 37% increased conversion compared to the respective single metal nanoparticles. Our approach is advantageous to produce nanoparticles with clean surfaces with available catalytic sites, directly in the solid-state and in an environmentally friendly manner.